SACRED: Systematic Analysis for Climate Resilient Development - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
Physical climate vulnerability is often assessed using three key methodologies: indicator-based methods (e.g., a vulnerability index), model and GIS-based (quantitative approaches), and participatory approaches (e.g., cognitive mapping, interviews, and surveys). Each methodology has its own strengths and weaknesses and a combination of approaches is often considered ideal. With respect to physical risks and impacts, IFPRI maintains a framework labelled SACRED (Systematic Analysis for Climate Resilient Development). This framework has been applied throughout Africa as well as in Asia. A schematic of the framework is shown below. Key features of the SACRED framework are: · Focus on a country or region rather than the globe. · Structural approach. The component models of the SACRED framework are typically bottom-up and drawn from first principles. · Completeness. All relevant climate change impact channels are treated in a coherent framework. · Flexibility. It is important that the elements of the SACRED modelling interact appropriately with one another; however, the exact modelling frameworks are flexible. · Risk and uncertainty. The SACRED framework is on the cutting edge when it comes to incorporating the likely frequency, severity, and economic implications of extreme events. Relative to many integrated assessment model (IAM) frameworks, the SACRED framework is detailed with granular representations of key features such as water systems, agriculture, and infrastructure. In addition, the economic model within SACRED has strong detail in water and in regional agriculture. As a result, it meshes well with the bio-physical modelling approaches that are key to appropriately representing climate change within the economic model. Key components of the framework are: 1. Incorporating both climate uncertainty and weather variability. 2. Using biophysical modelling to evaluate climate/weather impact on agricultural production. 3. Using water and hydrological models to assess future climate impact on irrigation, hydropower, droughts, and flooding. 4. Using both climate and water models to inform the assessment of damages from extreme events such as flooding, storm surge, and salinization on agriculture, infrastructure, and other capital. 5. When necessary, using additional models to assess options for the energy sector and to compute changes in greenhouse gas emissions. 6. Using an economic model to assess impact on GDP, welfare, employment, prices, and trade.